Imaging Hydrological Processes in Headwater Riparian Seeps with Time‐Lapse Electrical Resistivity. Issue 1 (12th September 2016) - Williams, Mark R.; Buda, Anthony R.; Singha, Kamini; Folmar, Gordon J.; Elliott, Herschel A.; Schmidt, John P.
Abstract: Delineating hydrologic and pedogenic factors influencing groundwater flow in riparian zones is central in understanding pathways of water and nutrient transport. In this study, we combined two‐dimensional time‐lapse electrical resistivity imaging (ERI) (depth of investigation approximately 2 m) with hydrometric monitoring to examine hydrological processes in the riparian area of FD‐36, a small (0.4 km 2 ) agricultural headwater basin in the Valley and Ridge region of east‐central Pennsylvania. We selected two contrasting study sites, including a seep with groundwater discharge and an adjacent area lacking such seepage. Both sites were underlain by a fragipan at 0.6 m. We then monitored changes in electrical resistivity, shallow groundwater, and nitrate‐N concentrations as a series of storms transitioned the landscape from dry to wet conditions. Time‐lapse ERI revealed different resistivity patterns between seep and non‐seep areas during the study period. Notably, the seep displayed strong resistivity reductions (∼60%) along a vertically aligned region of the soil profile, which coincided with strong upward hydraulic gradients recorded in a grid of nested piezometers (0.2‐ and 0.6‐m depth). These patterns suggested a hydraulic connection between the seep and the nitrate‐rich shallow groundwater system below the fragipan, which enabled groundwater and associated nitrate‐N to discharge through the fragipan to the surface. In contrast, time‐lapse ERI indicated no such connections in the non‐seep area, with infiltrated rainwater presumably perched above the fragipan. Results highlight the value of pairing time‐lapse ERI with hydrometric and water quality monitoring to illuminate possible groundwater and nutrient flow pathways to seeps in headwater riparian areas. Abstract : Article impact statement : Time‐lapse electrical resistivity imaging maps subsurface hydrological connections between riparian seeps and shallow groundwater.